Environmental sustainability in the gulf cooperation council (GCC) countries: The role of digitalization and planetary adjusted human development - Alsabhan, Talal H.; Anas, Muhammad (Sustainable futures, 2025)
As the urgency to combat climate change and its worsening consequences increases, scholars and policymakers are increasingly turning their attention to both digitalization and sustainable human development. These strategies are essential for improving environmental effectiveness and tackling climate change challenges. Consequently, investigations into the effects of digital transformation and sustainable human development on ecological sustainability have significantly increased recently. Hence, this paper aimed to investigate the effect of digitalization (DIGI), planetary pressures-adjusted human development (PHDI), productive capacity (PCI) and quality of institutions INSTQ on environmental sustainability in Gulf Cooperation Council (GCC) countries over the period from 2000 to 2021. Based on a CS-ARDL model with further verification through the use of CCEMG and AMG techniques, it is concluded that digitalization and PHDI improvement help in decreasing per capita carbon emissions (PC CO2), thus providing support for environmental sustainability. In contrast, the negative impact of PCI and INSTQ is not statistically significant. The results indicate that combining digitalization with human development is crucial for sustainable environmental results in the GCC region. [Display omitted]